2022
DOI: 10.1111/ajt.16937
|View full text |Cite
|
Sign up to set email alerts
|

Live virus vaccination following pediatric liver transplantation: Outcomes from two academic children’s hospitals

Abstract: Pediatric liver transplant (LT) recipients are often transplanted at a young age, precluding them from receiving live virus vaccinations (LVV) such as varicella (VZV) vaccine and measles, mumps and rubella. This places them at profound risk for vaccine preventable illness. We sought to detail safety of vaccination. This was a retrospective cohort study of pediatric LT recipients at two children's hospitals. Among 204 LT recipients included in the study, 97 received at least one LVV after LT. Six patients who d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…41,49,50 Therefore, cut-off levels for leukocytes >3000/μL, lymphocytes >1220/μL, IgG level >5 g/L, IgM level >0. but other prospective studies did not provide any equivalent information. 36,37,39 Table 2 summarizes the selection criteria used in vaccination trials in LT with MMR vaccines. Furthermore, even within the LIVE VAC study cohort, very large differences in eligibility criteria are found between the study centers.…”
Section: Cons Ider Ations and Requirements Reg Arding Mmr Vaccinati O...mentioning
confidence: 99%
“…41,49,50 Therefore, cut-off levels for leukocytes >3000/μL, lymphocytes >1220/μL, IgG level >5 g/L, IgM level >0. but other prospective studies did not provide any equivalent information. 36,37,39 Table 2 summarizes the selection criteria used in vaccination trials in LT with MMR vaccines. Furthermore, even within the LIVE VAC study cohort, very large differences in eligibility criteria are found between the study centers.…”
Section: Cons Ider Ations and Requirements Reg Arding Mmr Vaccinati O...mentioning
confidence: 99%
“…Measles vaccination of severely immunocompromised individuals has been contraindicated since the 1960s, when in one study, 1 of 8 children with underlying leukemia received attenuated measles vaccine and died 3 months after vaccination, though autopsy histopathology did not confirm measles as the cause of death 92 . Recent studies have described the safety and immunogenicity of MMR in seronegative liver and kidney transplant recipients receiving low‐level immunosuppression who had not received two doses of a measles‐containing vaccine prior to SOT 93–100 . The American Society of Transplantation and proceedings from an expert consensus meeting have since published recommendations for MMR vaccination after SOT in certain pediatric kidney and liver recipients, based on available data 28,101 .…”
Section: Measles Prevention After Transplantmentioning
confidence: 99%
“…92 Recent studies have described the safety and immunogenicity of MMR in seronegative liver and kidney transplant recipients receiving low-level immunosuppression who had not received two doses of a measlescontaining vaccine prior to SOT. [93][94][95][96][97][98][99][100] The American Society of Transplantation and proceedings from an expert consensus meeting have since published recommendations for MMR vaccination after SOT in certain pediatric kidney and liver recipients, based on available data. 28,101 To be considered eligible for MMR vaccination post-SOT, the pediatric liver or kidney recipient should be clinically well, ≥1 year post-SOT, ≥2 months after any acute graft rejection treatment episode, and meet specific criteria for a "low-level" net state of immune suppression.…”
Section: Me a S Le S Pre Venti On Af Ter Tr An S Pl Antmentioning
confidence: 99%
“…We identified 25 reports, including clinical research, case series, and case studies, on the use of live vaccines in patients receiving immunosuppressants [ 21 45 ]. Many of the patients involved had undergone solid organ transplants, and a large proportion were children (Table 3 ).…”
Section: Reports In the Literature On The Use Of Live Attenuated Vacc...mentioning
confidence: 99%